(untitled) (Práxis Educativa, 2020)
The pandemic caused by COVID-19, the so-called “new coronavirus” (SARS-CoV-2), was declared by the World Health Organization on March 11, 2020. Since then, the social, economic, health, political and scientific impacts have challenged scientists around the world. Especially in contexts of economic, social and school inequalities, the effects have been devastating. At the same time, alternatives created during this process need to be analyzed and understood. In this context, this article discusses the pedagogical practices proposed for children with Congenital Zika Virus Syndrome, during the period of social isolation caused by the Coronavirus pandemic. The research is qualitative and is based on the analysis of local documents on remote education and on semi-structured interviews carried out with five Education professionals from a teaching network in Baixada Fluminense, Rio de Janeiro, Brazil, who participated in a Pilot Continuing Education Program to act with children with Congenital Zika Virus Syndrome. For the analysis, the data were organized in thematic axes, showing, among other aspects, the teaching effort to develop online actions that promote interaction and participation of children in the proposed activities, in partnership with the mothers. They also show how the pandemic affected the relationship of the school with the family and the teachers’ persistence/resilience in the face of the numerous challenges posed by the pandemic in their teaching performance. Keywords: Congenital Zika Virus Syndrome. Remote teaching. Pedagogical practices.